Prospects and Challenges of Trade Policy to Karnali Province Government - Timilsena, Chhetra Mani; Kathayat, Bhupal Bikram (Journal of Entrepreneurship & Management Studies, 2024)
The study intended to explore the prospects and challenges of trade policy to Karnali Province Government. The study was set up since there was no trade policy formulated by the Karnali Province Government till the date. The study has also consulted the trade policy of Uttar Pradesh and Bihar based on province level and India, China, and the United States as well for national level. It has been explored based on the major five constructs such as socio-economic condition, trade education, geographical condition, connectivity and networking as well as the government priority. The study adopted mixed method research design guided by pragmatic research philosophy. The primary data were collected from political leaders, businessmen, critics and think-tank and ordinary consumer of Karnali Province. The tool for data collection was questionnaire. The study found there are many challenges to Karnali Province government in terms of socio-economic condition, trade education, geographical condition and the connectivity and networking as well as the government priority, however the government can grab them as the opportunities by conducting relevant researches and consulting with all the stakeholders.